Crew of whaling schooner Era preparing for floe whaling, Repulse Bay, Hudson Bay, Canada - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1902)
View of whaleboats and the whaling schooner Era, with ""the house over the after part of the vessel.still on"", Repulse Bay, Hudson Bay, Canada, May 3, 1902. Snow or ice can be seen in the foreground. Men identified as crew are engaged in readying the whaleboats for ""Floe Whaling."" Also identified in the scene are musk ox skins drying and a man drying bearskins. Infrastructure Livelihood Title supplied by cataloger. Information from original envelope identifies this as # 99. Photo would have been taken in the spring, during the season of floe whaling. During this time of year the whaling schooner was still frozen into the harbor ice, so the whaleboats were hauled out to the floe edge [the edge of the land-fast ice] and launched in search of whales. The boats were also provided with covers and used for shelter. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment.